Multi-user interference and cross correlation effects of spline multiwavelet based cognitive radio network - Mathew, Manju (2013)
A multi-user Cognitive Radio (CR) network resolves the problem of spectrum under utilization and enables the deployment of new wireless applications in the fast growing wireless communication area. The unique feature of CR is its ability to use the vacant band while insuring minimum interference to adjacent users. So modulation and multiple access schemes insuring minimum interference are required for CR transmission. Multiwavelets are rarely considered in the field of wireless communication. They are orthogonal and symmetric waveforms with short support and can insure lower multiple access interference in a multi-user environment. Hence a multi-user CR network using B-spline multiwavelets of different orders is considered in this paper for evaluating the performance characteristics. The cross correlation and multi-user interference are derived and its effect on error performance of linear, quadratic and cubic wavelets are analyzed. Simulation results prove that the number of users within a network can be increased by using spline wavelets of different orders without compromising on error performance.